Functional adaptation of microbial communities from jet fuel-contaminated soil under bioremediation treatment: simulation of pollutant rebound - Korotkevych, Olesya; Josefiova, Jirina; Praveckova, Martina; Cajthaml, Tomas; Stavelova, Monika; Brennerova, Maria V (FEMS microbiology ecology, 2011)
To investigate the link between the functionality and the diversity of microbial communities under strong selective pressure from pollutants, two types of mesocosms that simulate natural attenuation and phytoremediation were generated using soil from a site highly contaminated with jet fuel and under air-sparging treatment. An increase in the petroleum hydrocarbon concentration from 4900 to 18,500 mg kg(-1) dw soil simulated a pollutant rebound (postremediation pollutant reversal due to residual contamination). Analysis of soil bacterial communities by denaturing gradient gel electrophoresis of PCR-amplified 16S rRNA gene fragments showed stronger changes and selection for a phylogenetically diverse microbial population in the mesocosms with pollutant-tolerant willow trees. Enumeration of the main subfamilies of catabolic genes characteristic to the site detected a rapid increase in the degradation potential of both systems. A marked increase in the abundance of genes encoding extradiol dioxygenases with a high affinity towards various catecholic substrates was found in the planted mesocosms. The observed adaptive response to the simulated pollutant rebound, characterized by increased catabolic gene abundance, but with different changes in the microbial structure, can be explained by functional redundancy in biodegrading microbial communities.
Keywords: Soil Pollutants; Phylogeny; Molecular Sequence Data; Oxygenases; Bacteria; ropa; půda; Biodegradation, Environmental; oxygenasy; látky znečišťující půdu; biodegradace; Base Sequence; Hydrocarbons; fyziologická adaptace; sekvence nukleotidů; molekulární sekvence - údaje; půdní mikrobiologie; Soil Microbiology; fylogeneze; Adaptation, Physiological; Soil; Petroleum; uhlovodíky